Rapid Implementation of an Inpatient Telehealth Program during the COVID-19 Pandemic - Hron, Jonathan D.; Parsons, Chase R.; Williams, Lee Ann; Harper, Marvin B.; Bourgeois, Fabienne C. (Applied Clinical Informatics, 2020)
Background Relaxation of laws and regulations around privacy and billing during the COVID-19 pandemic provide expanded opportunities to use telehealth to provide patient care at a distance. Many health systems have transitioned to providing outpatient care via telehealth; however, there is an opportunity to utilize telehealth for inpatients to promote physical distancing.Objective This article evaluates the use of a rapidly implemented, secure inpatient telehealth program.Methods We assembled a multidisciplinary team to rapidly design, implement, and iteratively improve an inpatient telehealth quality improvement initiative using an existing videoconferencing system at our academic medical center. We assigned each hospital bed space a unique meeting link and updated the meeting password for each new patient. Patients and families were encouraged to use their own mobile devices to join meetings when possible.Results Within 7 weeks of go-live, we hosted 1,820 inpatient telehealth sessions (13.3 sessions per 100 bedded days). We logged 104,647 minutes of inpatient telehealth time with a median session duration of 22 minutes (range 1–1,961). There were 5,288 participant devices used with a mean of 3 devices per telehealth session (range 2–22). Clinicians found they were able to build rapport and perform a reasonable physical exam.Conclusion We successfully implemented and scaled a secure inpatient telehealth program using an existing videoconferencing system in less than 1 week. Our implementation provided an intuitive naming convention for providers and capitalized on the broad availability of smartphones and tablets. Initial comments from clinicians suggest the system was useful; however, further work is needed to streamline initial setup for patients and families as well as care coordination to support clinician communication and workflows. Numerous use cases identified suggest a role for inpatient telehealth will remain after the COVID-19 crisis underscoring the importance of lasting regulatory reform.
Keywords: COVID-19; coronavirus; telemedicine; inpatients; hospital medicine